Contact fatigue strength of 41CrAlMo7 grade steel by nitriding and shot-peening treatment - Nakonieczny, A.; Monka, G. (Фізико-хімічна механіка матеріалів, 2012)
This paper describes the method of raising contact fatigue strength, designated for application in the manufacture of gears. Investigations were carried out on 41CrAlMo7 grade steel (closest equivalent: Nitralloy 135M) following quenching and tempering, nitriding and double shot-peening. Special emphasis should be placed on the combination of the nitriding and shot-peening technologies. Both nitriding and shot-peening have been significantly modified and differ from the classical processes. Nitriding was carried out in such a way as to prevent the formation on the surface of a compound layer, composed of nitrides ε and γ. Shot-peening was carried out as a double stage operation, employing a change of parameters. As the result of combining the modernized processes, a new technology was developed, allowing the attaining of a contact fatigue limit that is comparable to that obtained by carburizing or induction hardening. The paper describes the methodology and the experimental work, as well as the achieved values of contact fatigue strength. Other surface parameters are also given, such as roughness, hardness, state and distribution of residual stresses. Описано метод підвищення контактної втомної міцності сталі для виробництва механічних приводів. Досліджено сталь 41CrAlMo7 (еквівалент: Nitralloy 135M) після гартування та відпуску, азотування та подвійної дробиноструминної обробки. Особливу увагу приділено поєднанню азотування та дробиноструминної обробки. Азотували так, щоб попередити утворення на поверхні складного шару з нітридів ε та γ. Дробино-струминну обробку виконували у два етапи, змінюючи параметри. В результаті створено нову технологію, що дає можливість досягати межі контактної втоми, яку можна порівняти з отриманою за навуглецювання чи індукційного зміцнення. Описан метод повышения контактной усталостной прочности стали для производства механических приводов. Исследована сталь 41CrAlMo7 (эквивалент: Nitralloy 135M) после закалки и отпуска, азотирования и двойной дробеструйной обработки. Особенное внимание обращено на сочетание азотирования и дробеструйной обработки. Азотировали так, чтобы предупредить образование на поверхности сложного слоя из нитридов ε и γ. Дробеструйную обработку выполняли в два этапа, изменяя параметры. В результате создана новая технология, которая дает возможность достигать предела контактной усталости, которую можно сравнить с полученной при науглероживании или индукционном упрочнении.